Corak Perbelanjaan dan Pengurusan Di Kalangan Beberapa Keluarga Melayu dan Cina Di Wilayah Persekutuan - Masud, Jariah (1982)
A study of the spending patterns and budgeting practices of Malay and Chinese housewives in Kuala Lumpur showed that more than 50% of the 173 families investigated had incomes of less than $600.00 per month. On the whole, Chinese families had larger incomes, spent more, and saved more than their Malay counterparts. The credit buying patterns of the two groups were similar, although about a third of both groups never used credit. It is suggested that education in the effective mpnagement of family resources could lead to an improvement in the quality of life of the families.